Purification and biochemical characterization of an alkaline protease from marine bacteria Pseudoalteromonas sp. 129‐1. (27th July 2015) - Wu, Shimei; Liu, Ge; Zhang, Dechao; Li, Chaoxu; Sun, Chaomin
Abstract : An extracellular alkaline protease produced by marine bacteria strain Pseudoalteromonas sp. 129‐1 was purified by ammonium sulphate precipitation, anion exchange chromatography, and gel filtration. The purity of the protease was confirmed by SDS–PAGE and molecular mass was estimated to be 35 kDa. The protease maintained considerable activity and stability at a wide temperature range of 10–60 °C and pH range of 6–11, and optimum activity was detected at temperature of 50 °C and pH of 8. Metallo‐protease inhibitor, EDTA, had no inhibitory effect on protease activity even at concentration up to 15 mM, whereas 15 mM PMSF, a common serine protease inhibitor, greatly inactivated the protease. The high stability of the protease in the presence of surfactants (SDS, Tween 80, and Triton X‐100), oxidizing agent H2 O2, and commercial detergents was observed. Moreover, the protease was tolerant to most of the tested organic solvents, and saline tolerant up to 30%. Interestingly, biofilm of Pseudomonas aeruginosa PAO1 was greatly reduced by 0.01 mg ml −1 of the protease, and nearly completely abolished with the concentration of 1 mg ml −1 . Collectively, the protease showed valuable feathers as an additive in laundry detergent and non‐toxic anti‐biofilm agent.